Characterisation of a plancitoxin-1-like DNase II gene in Trichinella spiralis. - Chengshui Liao; Mingyuan Liu; Xue Bai; Pan Liu; Xuelin Wang; Tingting Li; Bin Tang; He Gao; Qingsong Sun; Xidong Liu; Ying Zhao; Feng Wang; et al. (Public Library of Science (PLoS), 2014)
Deoxyribonuclease II (DNase II) is a well-known acidic endonuclease that catalyses the degradation of DNA into oligonucleotides. Only one or a few genes encoding DNase II have been observed in the genomes of many species. 125 DNase II-like protein family genes were predicted in the Trichinella spiralis (T. spiralis) genome; however, none have been confirmed. DNase II is a monomeric nuclease that contains two copies of a variant HKD motif in the N- and C-termini. Of these 125 genes, only plancitoxin-1 (1095 bp, GenBank accession no. XM_003370715.1) contains the HKD motif in its C-terminus domain.In this study, we cloned and characterised the plancitoxin-1 gene. However, the sequences of plancitoxin-1 cloned from T. spiralis were shorter than the predicted sequences in GenBank. Intriguingly, there were two HKD motifs in the N- and C-termini in the cloned sequences. Therefore, the gene with shorter sequences was named after plancitoxin-1-like (Ts-Pt, 885 bp) and has been deposited in GenBank under accession number KF984291. The recombinant protein (rTs-Pt) was expressed in a prokaryotic expression system and purified by nickel affinity chromatography. Western blot analysis showed that rTs-Pt was recognised by serum from T. spiralis-infected mice; the anti-rTs-Pt serum recognised crude antigens but not ES antigens. The Ts-Pt gene was examined at all T. spiralis developmental stages by real-time quantitative PCR. Immunolocalisation analysis showed that Ts-Pt was distributed throughout newborn larvae (NBL), the tegument of adults (Ad) and muscle larvae (ML). As demonstrated by DNase zymography, the expressed proteins displayed cation-independent DNase activity. rTs-Pt had a narrow optimum pH range in slightly acidic conditions (pH 4 and pH 5), and its optimum temperature was 25°C, 30°C, and 37°C.This study indicated that Ts-Pt was classified as a somatic protein in different T. spiralis developmental stages, and demonstrated for the first time that an expressed DNase II protein from T. spiralis had nuclease activity.